Penerapan Konsep Halal dalam Industri Farmasi dan Kosmetik di Indonesia: Implementation of Halal Concepts in Indonesia's Pharmaceutical and Cosmetic Industries: A Review of Raw Materials, Production Processes, Halal Certification, and Cosmetic Trends - Ana Fauziah; Dea Amanda Hafizhah; Lisnawati (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2026)
The halal pharmaceutical and cosmetic industries are sectors that continue to grow in line with increasing public awareness of the importance of using products that comply with Islamic principles. Indonesia, as a country with a predominantly Muslim population, has significant potential for the development of the halal industry, particularly in the pharmaceutical and cosmetic sectors. This study aims to examine the implementation of halal concepts in the pharmaceutical and cosmetic industries in Indonesia through a review of raw materials, production processes, halal certification, and the development of halal cosmetic trends. The research employed a descriptive qualitative method using a literature review approach based on scientific journals, books, regulations, and related documents. The findings indicate that the implementation of halal principles is determined not only by the halal status of raw materials but also by production processes, storage, distribution, and the halal assurance system implemented by companies. Halal certification administered by the Halal Product Assurance Organizing Agency (BPJPH) and supported by LPPOM MUI plays an important role in ensuring product halalness, enhancing consumer trust, and strengthening industrial competitiveness. In addition, the halal cosmetic market in Indonesia has shown significant growth due to increasing consumer demand for products that are safe, high-quality, and compliant with Islamic values. Therefore, synergy among the government, certification bodies, and industry stakeholders is needed to support the sustainable development of the halal pharmaceutical and cosmetic industries.